Ways to Improve the Efficiency of Devices for Freezing of Small Products - Bazaluk, Oleg; Стручаєв, Микола Іванович; Struchaiev, Mykola; Halko, Serhii; Галько, Сергій Віталійович; Miroshnyk, Oleksandr; Bondarenko, Larysa; Бондаренко, Лариса Юріївна; Karaiev, Oleksandr; Караєв, Олександр Гнатович; Nitsenko, Vitalii (My University, 2022)
It has been established that one of the main problems in the technology of the production of loose food products is the sticking of vegetables or fruits into one block. It has been proven that one of the steps to solve this problem is the use of berries, fruits, or vegetables during freezing in the form of a fluidized bed in air. However, a significant part of the energy is spent precisely when creating a f luidized bed with the help of fans. By improving the separation efficiency of small products in the freezing process, it would be possible to significantly reduce the energy costs of freezing worldwide by the authors. The purpose of this work was to determine ways to increase the efficiency of devices for freezing small products. The goal was achieved through the use of a modified method for studying energy costs, taking into account energy costs for fluidization and mechanical shaking. For comparison, two options for the efficient separation of small products during freezing were considered. Namely the separation of small products in the process of freezing with the help of fluidization, and with the help of mechanical shaking. Comparison of these variants showed that it was advisable to separate small products during freezing by mechanical shaking. It was established that their energy parameters, as well as fractional properties, are significantly different. The product temperature was determined for the case of a constant temperature of the cooling air and equipment elements. The results obtained confirmed the possibility of achieving significant energy savings of 1.5–3.5 times by using the mechanized device we proposed for freezing fruits and vegetables. The main result of this paper is the proposed method, or algorithm, for calculating energy costs for fluidization and mechanical shaking, which could be used in the design of devices for the freezing of small products; as well as the obtained data confirming the correspondence of the theoretical calculations to reality. The novelty of the research consists in presenting a model or algorithm for calculating the energy costs for fluidization and mechanical shaking. The importance of the results of the work lies in the possibility of using this technique to assess the energy effectiveness of devices for the freezing of small products.
Keywords: mechanized device; small-piece; fluidized bed; quick freezing; fruit and vegetable; energy savings; experimental studies; thermal conductivity; equivalent diameter; time of pre-freezing; heat capacity; energy consumption; cascade freezer; result; graph; analysis